Die Röntgenologie im Licht der Evolutionären Erkenntnistheorie - Gelinsky, Paul (DMW - Deutsche Medizinische Wochenschrift, 2017)
An X-ray photograph is not adapted to the human a priori intuition: it is not colored, it is two-dimensional, has no depth and no perspective. A radiograph is composed by about 100 gradations of grey, of which the human eye cannot resolve more than 30. Projection radiography has a cardinal problem: the superposition of normal and pathological structures. Apart from visual physiology, visual psychology plays an essential role in diagnosis: expectation and stereotyped thinking influence the interpretation of visual perception. X-ray findings are to be compared with anamnesis, laboratory values, clinical data and always with good judgement – this was already known in 1913. Plato sketched a cave analogy that describes the difficulties of interpreting „shadows“ – with very interesting parallels to radiology.
Keywords: Röntgenologie; Evolutionäre Erkenntnistheorie; Mesokosmos; Befund; Platon; Höhlengleichnis